Advanced numerical modelling of the nonlinear mechanical behaviour of a laterally loaded pile embedded in stiff unsaturated clay - Braun, Kevin T.; Bakas, Nikolaos P.; Markou, George; Jacobsz, S. W. (My University, 2023)
Capturing and understanding the ultimate limit state behaviour of reinforced concrete piles embedded in soil requires the use of advanced tools or the performance of expensive tests. An experiment was performed where reinforced concrete piles embedded in a stiff unsaturated clay profile were load-tested on-site. However, even though in-situ experiments can provide engineers with valuable insight, their cost and time limitations come with restrictions, especially when dealing with a parametric investigation on the soil’s material properties, the size of the piles, or the piles’ material properties. The objective of this research work was to numerically model the nonlinear mechanical behaviour of laterally loaded full-scale piles through detailed 3D modelling, and perform an in-depth parametric investigation to provide answers to unknown factors that the actual physical experiment could not answer. Furthermore, this work serves as a pilot project that will be used to pave the way in developing multiple soil-structure interaction models that will be used to generate a dataset that helps the creation of predictive models through machine learning algorithms. For the needs of this research work, the reinforced concrete piles were discretised with 8-noded isoparametric hexahedral elements that accounted for cracking through the smeared crack approach. Steel reinforcement bars and stirrups were simulated as embedded rebar elements, while the soil domain was also discretised through 8-noded hexahedral elements. Most of the required material properties assumed during the nonlinear analyses were defined according to relevant laboratory experiments. According to the numerical investigation, it was found that the proposed numerical model has the ability to reproduce the experimental results with high accuracy, while providing in-depth insight on the failure mechanisms for both the soil and reinforced concrete domains.
Keywords: Soil-structure interaction; Reinforced concrete pile; Soil domain; Mechanical behaviour; Finite Element Method